Do physician incentives increase patient medication adherence?. (22nd July 2020) - Kong, Edward; Beshears, John; Laibson, David; Madrian, Brigitte; Volpp, Kevin; Loewenstein, George; Kolstad, Jonathan; Choi, James J.
Abstract: Objective: To test the effectiveness of physician incentives for increasing patient medication adherence in three drug classes: diabetes medication, antihypertensives, and statins. Data Sources: Pharmacy and medical claims from a large Medicare Advantage Prescription Drug Plan from January 2011 to December 2012. Study Design: We conducted a randomized experiment (911 primary care practices and 8, 935 nonadherent patients) to test the effect of paying physicians for increasing patient medication adherence in three drug classes: diabetes medication, antihypertensives, and statins. We measured patients' medication adherence for 18 (6) months before (after) the intervention. Data collection/extraction methods: We obtained data directly from the health insurer. Principal Findings: We found no evidence that physician incentives increased adherence in any drug class. Our results rule out increases in the proportion of days covered by medication larger than 4.2 percentage points. Conclusions: Physician incentives of 50 per patient per drug class are not effective for increasing patient medication adherence among the drug classes and primary care practices studied. Such incentives may be more likely to improve measures under physicians' direct control rather than those that predominantly reflect patient behaviors. Additional research is warranted to disentangle whether physician effort is not responsive to these types of incentives, or medication adherence is not responsive to physician effort. Our results suggest that significant changes in the incentive amount or program design may be necessary to produce responses from physicians or patients.